Biomechanical Correlates of Surface Electromyography Signals Obtained During Swallowing by Healthy Adults. - Crary, Michael A.; Carnaby, Giselle D.; Groher, Michael E. (Journal of Speech, Language & Hearing Research, 2006)
Purpose: The purpose of this study was to describe biomechanical correlates of the surface electromyographic signal obtained during swallowing by healthy adult volunteers. Method: Seventeen healthy adults were evaluated with simultaneous videofluoroscopy and surface electromyography (sEMG) while swallowing 5 mL of liquid barium sulfate. Three biomechanical swallowing events were analyzed: hyoid elevation, pharyngeal constriction, and opening—closing of the pharyngoesophageal segment. For each biomechanical event and from the sEMG signal, the authors identified onset, peak, and offset time points. From these points, duration measures were calculated. Means and 95% confidence intervals were calculated for each measure. Subsequently, correlations were evaluated between timing aspects of the sEMG traces and each biomechanical event. Results: Swallow onset in the sEMG signal preceded the onset of all biomechanical events. All biomechanical events demonstrated a strong correspondence to the sEMG signal. The strongest relationship was between hyoid elevation—anterior displacement and the sEMG signal. Conclusions: These results suggest that the sEMG signal is a useful indicator of major biomechanical events in the swallow. Future studies should address the impact of age and disease processes, as well as bolus characteristics, on the biomechanical correlates of sEMG signals obtained during swallowing. Reprinted by permission of the publisher.